2016
DOI: 10.1111/bph.13423
|View full text |Cite
|
Sign up to set email alerts
|

Single administration of recombinant IL‐6 restores the gene expression of lipogenic enzymes in liver of fasting IL‐6‐deficient mice

Abstract: Lipogenesis is intimately controlled by hormones and cytokines as well as nutritional conditions. IL-6 participates in the regulation of fatty acid metabolism in the liver. We investigated the role of IL-6 in mediating fasting/re-feeding changes in the expression of hepatic lipogenic enzymes. EXPERIMENTAL APPROACHGene and protein expression of lipogenic enzymes were examined in livers of wild-type (WT) and IL-6-deficient (IL-6 À/À ) mice during fasting and re-feeding conditions. Effects of exogenous IL-6 admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…Finally, Ppar α KO mice were also exposed to a repeated vehicle or APAP administration for 3 days ( n = 6/group). Animals were fasted for 12 h before sacrifice to avoid food-induced changes in liver genes (Vida et al, 2015 ; Gavito et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Ppar α KO mice were also exposed to a repeated vehicle or APAP administration for 3 days ( n = 6/group). Animals were fasted for 12 h before sacrifice to avoid food-induced changes in liver genes (Vida et al, 2015 ; Gavito et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…For some experiments IL-6-deficient (IL-6 -/- ) mice, strain B6.129S2-IL-6 tm1Kopf /J (SN 2650, http://jaxmice.jax.org/strain/002650.html ), were also included. Since the levels of lipogenic enzymes in liver may vary depending on the time of food intake or fasting [ 36 ], both strains were maintained in the same feeding/fasting conditions. The day of sacrifice, animals were fasted from 08:00 h. The mice were treated with the last inoculation of rIL-6 or vehicle at 12:00 h and were sacrificed 1 hour later.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, treatment of mice with IL-6 increases the levels of Stat3 mRNA in the liver [ 35 ]. Moreover, we reported that the gene expression of the lipogenic enzymes Acac, Fas and Stearoyl-CoaA desaturase (Scd1) was no longer up-regulated by IL-6 in the presence of siRNA Stat3 in hepatocytes, therefore indicating that IL-6-mediated signalling promotes the expression of these enzymes via activation of Stat3 [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations